Household’s demand for Food Commodities in Pakistan: Issues and Empirical Evidence - Akram, Naeem (Estudios de Economía, 2020)
The household’s demand analysis is very crucial in the sense that undernourishment negatively affects productivity. Food demand is crucial to gauge the household’s ability or willingness to purchase/consume different food commodities. The study attempts to analyze the household’s food demand in Pakistan by estimating the Quadratic Almost Ideal Demand System (QUAIDS) on Household Integrated Income and Consumption Survey (HIICS) 2015-16 data. It has been found that the household’s locality, dependency ratio, living in own house, age and level of education of household head have significant impacts on demand for different food commodities. It has been further found that hoteling, fruits & dry fruits, soft drinks & bottled water, bakery products, beef & mutton, chicken &seafood are luxury goods. Eggs, sugar & sweets, pulses, tea & coffee, vegetables, rice, and edible oil & ghee are necessity goods. The spices, milk & yogurt and wheat are close to sticky food items. The price elasticities suggest that the demand for beef & mutton, seafood, eggs, and soft drinks is relatively elastic in comparison to other food commodity groups. Moreover, the demand for tea & coffee is least elastic revealing that price of tea has a very marginal impact on its demand.